Legal Certainty in Green Bonds: The Role of Coherence, Legitimacy, Economic Benefits, and Government Authority - Hutahayan, Benny; Fadli, Moh.; Amimakmur, Satria Amiputra; Dewantara, Reka; Tumanggor, Manumpan S.; Djajadikerta, Hadrian Geri (Jurnal Hukum, 2024)
This study explores the critical factors shaping legal certainty in green bond issuance, focusing on the roles of coherence in bond issuance objectives, legislative legitimacy, economic benefits, and governmental authority. Legal certainty is essential in fostering investor confidence, reducing risks such as greenwashing, and ensuring compliance with environmental and regulatory standards. The research employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze data collected from institutional investors with a recommended sample of 300 participants, revealing that economic benefits have the most significant impact on legal certainty, followed by governmental authority, legislative legitimacy, and coherence of objectives. The results underscore the importance of clear and measurable objectives in green bond issuance, transparency in the legislative process, and consistent governmental oversight. These findings highlight the need for robust legal frameworks that ensure both environmental sustainability and financial stability. The study's implications suggest that policymakers and regulators must prioritize the harmonization of green bond regulations to promote cross-border investments and long-term market growth.